(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
Issues such as students’ lack of confidence when it comes to participating in math class and understanding the topics before tackling the proposed problems and exercises, very traditional and non engaging teaching methods from educators, students’ complacency in their learning process, boredom, "fear," or hatred towards the subject, among other factors, all play a role. Additionally, some strategies are presented to foster interest in mathematics and boost motivation in students when it comes to learning and actively participating in the subject. The main goal is to share these strategies. All of this was carried out based on 13 documents found in the Google Scholar database using the search equation Mathematics AND motivation AND learning AND “secondary education.” These documents address the chosen topic and strategies to counter the issue. In conclusion, these different articles discuss various aspects of math education, from the importance of learning it to the use of strategies to motivate students when learning mathematics.